Physiological hypoxia improves growth and functional differentiation of human intestinal epithelial organoids - Walaas, Gunnar Andreas; Gopalakrishnan, Shreya; Bakke, Ingunn; Skovdahl, Helene Kolstad; Flatberg, Arnar; Østvik, Ann Elisabet; Sandvik, Arne Kristian; Bruland, Torunn (Frontiers in Immunology, 2023)
Background: The epithelium in the colonic mucosa is implicated in the pathophysiology of various diseases, including inflammatory bowel diseases and colorectal cancer. Intestinal epithelial organoids from the colon (colonoids) can be used for disease modeling and personalized drug screening. Colonoids are usually cultured at 18-21% oxygenwithout accounting for the physiological hypoxia in the colonic epithelium(3% to <1% oxygen) We hypothesize that recapitulating the in vivo physiological oxygen environment (i.e., physioxia) will enhance the translational value of colonoids as pre-clinical models. Here we evaluate whether human colonoids can be established and cultured in physioxia for the entire in vitro culture period and compare growth, differentiation, and immunological responses at 2% and 20% oxygen. Methods: Growth from single cells to differentiated colonoids was monitored by brightfield images and evaluated with a linear mixed model. Cell composition was identified by immunofluorescence staining of cell markers and single-cell RNA-sequencing (scRNA-seq). Enrichment analysis was used to identify transcriptomic differences within cell populations. Pro-inflammatory stimuli induced chemokines and Neutrophil gelatinase-associated lipocalin (NGAL) release were analyzed by Multiplex profiling and ELISA. Direct response to a lower oxygen level was analyzed by enrichment analysis of bulk RNA sequencing data. Results: Colonoids established in a 2% oxygen environment acquired a significantly larger cell mass compared to a 20% oxygen environment. No differences in expression of cell markers for cells with proliferation potential (KI67 positive) , goblet cells (MUC2 positive), absorptive cells (MUC2 negative, CK20 positive) and enteroendocrine cells (CGA positive) were found between colonoids cultured in 2% and 20% oxygen. However, the scRNA-seq analysis identified differences in the transcriptome within stem-, progenitor- and differentiated cell clusters. Both colonoids grown at 2% and 20% oxygen secreted CX3CL1, CXCL2, CXCL5, CXCL6, CXCL10, CXCL12, CCL20, CCL25, and NGAL upon TNF + poly(I:C) treatment,but there appeared to be a lower pro-inflammatory response in 2% oxygen. Reducing the oxygen environment from 20% to 2% in differentiated colonoids altered the expression of genes related to differentiation, metabolism, mucus lining, and immune networks. Conclusions: Our results suggest that colonoids studies can and should be performed in physioxia when the resemblance to in vivo conditions is important.